Futech Web Ordering System - An Integration of Supply Chain Management Approach - Liang, Shieh Wen (2003)
The purpose of this project is to develop an online Futech Web Ordering System for the Futech Computer Ltd. Futech Computer Ltd is a computer store, one of the retailer companies that carry a narrow product line with a deep assortment within that line. The reasons to develop the online system for the company are that Internet has become an enormously popular marketing paradigm that facilitates anything consumers want to shop for or buy on the Web. Through the Internet online system, the market of the company can be expanded over the world. The management can get the customers feedback and requirement quickly, the customers feel more convenient to search the products they want because the electronic shop-front is open 24 hours a day, to the entire world. Besides that, the online system also can help the company to manage the information or record inside the company more effectively and efficiently. The methodology chooses to use to develop the online system comprises a sequence from one phase to the next involving together four phases. The phases are system analysis, system design, system development and the system testing. System analysis is the process of gathering information about the current system and the user requirements and analysis the information. System design decides how to build the new system. In the system development phase, the software and programming language use to develop the system. Finally the system will be tested in the system-testing phase before fully implemented.